2023
DOI: 10.1523/jneurosci.1451-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Affective Functions of the Cerebellum

Stephanie Rudolph,
Aleksandra Badura,
Stefano Lutzu
et al.

Abstract: The cerebellum, traditionally associated with motor coordination and balance, also plays a crucial role in various aspects of higher-order function and dysfunction. Emerging research has shed light on the cerebellum's broader contributions to cognitive, emotional, and reward processes. The cerebellum's influence on autonomic function further highlights its significance in regulating motivational and emotional states. Perturbations in cerebellar development and function have been implicated in various neurodeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 215 publications
0
9
0
1
Order By: Relevance
“…Tsien reflected on the function of the PNN by suggesting long-term memories were stored in the pattern made by these holes [ 246 ]. In a recent review, Rudolph et al noted PNNs restrict new synapses from being produced and old synapses from being pruned, which is thought to regulate neuronal plasticity [ 247 ]. This view was included among those described by Celio et al, who also provided evidence that the PNN may maintain cellular relationships, concentrate growth factors, generate an ion-buffering microenvironment, prevent extracellular space occlusion, and form a link with the intracellular cytoskeleton [ 205 ].…”
Section: The Perineuronal Netmentioning
confidence: 99%
“…Tsien reflected on the function of the PNN by suggesting long-term memories were stored in the pattern made by these holes [ 246 ]. In a recent review, Rudolph et al noted PNNs restrict new synapses from being produced and old synapses from being pruned, which is thought to regulate neuronal plasticity [ 247 ]. This view was included among those described by Celio et al, who also provided evidence that the PNN may maintain cellular relationships, concentrate growth factors, generate an ion-buffering microenvironment, prevent extracellular space occlusion, and form a link with the intracellular cytoskeleton [ 205 ].…”
Section: The Perineuronal Netmentioning
confidence: 99%
“…The cerebellum has long been known for its role in fine motor control and balance. A more recent appreciation has developed for broader cerebellar contributions to emotion and cognition and cerebellar dysfunction in autism spectrum disorder ( Van Overwalle et al, 2020 ; van der Heijden et al, 2021 ; Rudolph et al, 2023 ). Anatomical connectivity within cerebellar circuits is well understood, particularly for the cerebellar cortex ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…During a recent analysis of genes associated with myoblast DMRs, we found that ZNF556 (Zinc Finger Protein 556) has a strong preference for expression in both myoblasts and cerebellum, as described below. In a previous study of myoblast epigenetics using reduced representation bisulfite sequencing (RRBS) profiles, we identified CDH15 (Cadherin 15), as a gene also displaying myoblast and cerebellum-specific expression [13]. Cerebellum is critical for motor coordination, cognition, and emotional processes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebellum is critical for motor coordination, cognition, and emotional processes [14]. It is quite distinct morphologically and functionally from other brain regions and is important in neuromuscular disease [15]. Its transcriptome is strikingly distinct from those of all the other brain regions [16].…”
Section: Introductionmentioning
confidence: 99%